Personal exposure to particulate PAHs and anthraquinone and oxidative DNA damages in humans - Wei, Yongjie; Han, In-Kyu; Hu, Min; Shao, Min; Zhang, Junfeng(Jim); Tang, Xiaoyan (Chemosphere (Oxford), 2010)
Recent studies suggest that DNA oxidative damage be related to the chemical constituents of ambient particles. The purpose of this study was to examine whether particulate polycyclic aromatic hydrocarbons (PAHs) and quinone-structure chemicals increase body burden of oxidative stress in human exposed to heavy traffic volume. We recruited two nonsmoking security guards who worked at a university campus gate near a heavily trafficked road. Each subject wore a personal air sampler for 24 h per day to estimate exposures to 24 PAHs and anthraquinone (AnQ) in PM 2.5. Daily pre- and post-work shift spot urines were collected for 29 d from each subject. Urine samples were analyzed for 8-hydroxy-2′-deoxyguanosine (8-OHdG). Additionally, using 19 organic tracers other than 24 PAHs and AnQ, a receptor source apportionment model of chemical mass balance was applied to determine the contributions of sources on the PM: gasoline vehicle, diesel vehicle, coal burning, vegetable debris, cooking, natural gas and biomass burning. The relationship among urinary 8-OHdG, individual PAH, and AnQ was demonstrated as follows: the average urinary concentration of 8-OHdG was increased more than three times after 8-h work-shift than those before the work shift. All the 24 PAH and AnQ levels were positively and significantly associated with the post-work urinary 8-OHdG. The results from source apportionment suggest vehicular emission to be the dominant source of personal exposure to PM 2.5. Our finding indicates that personal air exposures to 24 individual PAHs and AnQ originating from traffic emissions are important in increasing oxidative burdens in human body.